The theory and method of design and optimization for Railway Intelligent Transportation Systems (RITS) - Wang, Zhuo ([Bentham Science Publishers], 2011)
This book explains the theory and methods of system optimization design for railway intelligent transportation systems (RITS), which optimizes RITS total performance by decreasing the difficulty and cost of system development and increasing the system efficiency. Readers will understand key concepts of RITS and the latest research relevant to China and other countries where RITSs have been developed. The book is suitable for university scholars in the field of railway transportation.